Altered PVN‐to‐CA2 hippocampal oxytocin pathway and reduced number of oxytocin‐receptor expressing astrocytes in heart failure rats. (3rd June 2022) - Althammer, Ferdinand; Roy, Ranjan K.; Lefevre, Arthur; Najjar, Rami S.; Schoenig, Kai; Bartsch, Dusan; Eliava, Marina; Feresin, Rafaela G.; Hammock, Elizabeth A. D.; Murphy, Anne Z.; Charlet, Alexandre; Grinevich, Valery; et al.
Abstract: Oxytocinergic actions within the hippocampal CA2 are important for neuromodulation, memory processing and social recognition. However, the source of the OTergic innervation, the cellular targets expressing the OT receptors (OTRs) and whether the PVN‐to‐CA2 OTergic system is altered during heart failure (HF), a condition recently associated with cognitive and mood decline, remains unknown. Using immunohistochemistry along with retrograde monosynaptic tracing, RNAscope and a novel OTR‐Cre rat line, we show that the PVN (but not the supraoptic nucleus) is an important source of OTergic innervation to the CA2. These OTergic fibers were found in many instances in close apposition to OTR expressing cells within the CA2. Interestingly, while only a small proportion of neurons were found to express OTRs (~15%), this expression was much more abundant in CA2 astrocytes (~40%), an even higher proportion that was recently reported for astrocytes in the central amygdala. Using an established ischemic rat heart failure (HF) model, we found that HF resulted in robust changes in the PVN‐to‐CA2 OTergic system, both at the source and target levels. Within the PVN, we found an increased OT immunoreactivity, along with a diminished OTR expression in PVN neurons. Within the CA2 of HF rats, we observed a blunted OTergic innervation, along with a diminished OTR expression, which appeared to be restricted to CA2 astrocytes. Taken together, our studies highlight astrocytes as key cellular targets mediating OTergic PVN inputs to the CA2 hippocampal region. Moreover, they provide the first evidence for an altered PVN‐to‐CA2 OTergic system in HF rats, which could potentially contribute to previously reported cognitive and mood impairments in this animal model. Abstract : The consequences of myocardial infarction on the hypothalamic oxytocin system are not well understood. Here we studied the effect of heart failure on oxytocin receptor expression and oxytocin fiber density in dorsal CA2 using our established heart failure rat model. We observed significant reductions in OTR mRNA and protein levels, OT fiber density as well as a reduction in the number of OTR‐positive astrocytes. This is the first study reporting OTR‐positive astrocytes in the rat hippocampus and provides unprecedented evidence that cardiovascular disease can alter astrocytic OTR signaling.